FIQIH LEMBAGA PERBANKAN SYARIAH - Habib Yasin Al Quds; Siti Alya Ismayanti; Muhammad Azzam Izudin; Iwan Setiawan; Nema Widiantini (UIN Sunan Gunung Djati Bandung, 2025)
This study presents a comprehensive analysis of the implementation of the principles of fiqh muamalah in the Indonesian Islamic banking system. Using a qualitative descriptive-analytical approach, this study examines three main aspects: (1) the application of sharia principles in banking operations, (2) the perspectives of contemporary scholars on sharia banking practices, and (3) strategic challenges along with recommendations for solutions. The research findings reveal that although Islamic banking has successfully adopted various sharia contracts such as mudharabah, musyarakah, and murabahah, there are still significant challenges in terms of the consistency of the application of sharia principles, product innovation, and public literacy. This study makes an important contribution by presenting a holistic development framework that integrates sharia, regulatory, and business practice aspects to strengthen the position of Islamic banking in the national financial system.